Pengaruh Pembiayaan Modal Kerja dan Investasi Terhadap NPF Bank Umum Syariah di Jawa Barat Periode 2021-2023 - Wulan Rindyana S; Jaharuddin Jaharuddin (CV. Ulil Albab Corp, 2024)
This research investigates the impact of managing working capital and investment funding on the level of Non-Performing Financing (NPF) in Islamic banks located in West Java from 2021 to 2023. Islamic banks, integral to the financial system, uphold Sharia principles in all operations, crucially supporting regional economic growth. A key challenge for these banks is managing the NPF rate, influenced by effective working capital and investment strategies. The study underscores the significance of these strategies in reducing NPF rates, emphasizing proper management as pivotal. Bank management must consistently prioritize these strategies to mitigate credit risks and enhance overall financial performance. The study employed time series analysis of secondary data from financial statements of West Java's Islamic commercial banks during the specified period, revealing significant correlations between working capital financing, investment, and NPF rates.